Properties of particleboard from Kelempayan (Anthocepalus chinensis) at 450 kg/m3 with 8%, 10% and 12% resin / Hafizudin Mohd - Mohd, Hafizudin (2004)
In this study, three percentage of resin urea-fonna1dehyde (UF) that are 8%, 10% and 12% resin will be mixed with the Anthocepalus chinensis wood particles. This mixed will be made a board that called particleboard after been cured by heat and pressure. The properties of this board will be determined by several types of test. The result shows that the percentage of resin used are affecting the properties of the board. From this project only the bending strength not reach the value than been specified.